1980
DOI: 10.1002/ana.410080509
|View full text |Cite
|
Sign up to set email alerts
|

Lymph nodes—A possible site for sympathetic neuronal regulation of immune responses

Abstract: Noradrenergic fibers were identified in rat cervical lymph nodes by fluorescence histochemistry and confirmed by radioenzymatic determination of norepinephrine. After superior cervical ganglionectomy, lymph node norepinephrine and noradrenergic fluorescence were strikingly decreased. The alpha-adrenergic radioligand [3H] dihydroergocryptine bound to saturable sites on lymph node membranes (0.20 pmol/mg protein; affinity constant, 8 nM) with characteristics expected for alpha-adrenergic receptor binding. The al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(30 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…38 -41 Aside from supplying ocular structures, the sympathetic nerves that originate in the SCG also supply lymph nodes thought to process intraocular antigens including the cervical and submandibular lymph nodes. 42,43 In agreement with our results, prior studies have identified alterations in immune responsiveness within these lymph nodes as a result of SCGX. They include enhanced contact hypersensitivity, DTH, and graft versus host reactions.…”
Section: Discussionsupporting
confidence: 93%
“…38 -41 Aside from supplying ocular structures, the sympathetic nerves that originate in the SCG also supply lymph nodes thought to process intraocular antigens including the cervical and submandibular lymph nodes. 42,43 In agreement with our results, prior studies have identified alterations in immune responsiveness within these lymph nodes as a result of SCGX. They include enhanced contact hypersensitivity, DTH, and graft versus host reactions.…”
Section: Discussionsupporting
confidence: 93%
“…The distribution of sympathetic nerves has been described in the lymph nodes from rats [7,100,[109][110][111][112][113], several strains of mice [5,110,111,113,114], cats, pigs and humans [110]; however, the origin of the NA nerves in lymph nodes is still unclear. It is presumed that their innervation is regionally supplied as lymph nodes are regional structures draining the areas with which they are associated.…”
Section: The Lymph Nodesmentioning
confidence: 99%
“…It is presumed that their innervation is regionally supplied as lymph nodes are regional structures draining the areas with which they are associated. For example, in the rat when the superior cervical ganglia are removed, sympathetic nerves are lost in the cervical nodes [109]. NA nerves supplying the cervical, mesenteric and popliteal lymph nodes course along the vasculature that provides their blood supply [5,7,100,[109][110][111][112][113][114].…”
Section: The Lymph Nodesmentioning
confidence: 99%
“…Morphological studies indicate that lymph nodes are innervated by a variety of fibre types including adrenergic (Giron, Crucher & Davis, 1980;Felten, Livnat, Felten, Carlsen, Bellinger & Yeh, 1984), substance P-containing and calcitonin generelated peptide-containing (Popper, Mantyh, Vigna, Maggio & Mantyh, 1988) types. It has been suggested that these nerves might modulate the immune system since sympathetic denervation of lymph nodes or the spleen alters the immune responsiveness of these organs (Besedovsky, Del Rey, Sorkin, Da Prada & Keller, 1979;Felten et al 1984;Popper et al 1988).…”
Section: Introductionmentioning
confidence: 99%